1996
DOI: 10.1006/viro.1996.0059
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Diversity within the Reovirus S3 Gene: Reoviruses Evolve Independently of Host Species, Geographic Locale, and Date of Isolation

Abstract: To better understand genetic diversity of mammalian reoviruses, we studied sequence variability in the S3 gene segment of 17 field-isolate reovirus strains and prototype strains of the three reovirus serotypes. Strains studied were isolated over a 37-year period from different mammalian hosts and geographic locations. A high degree of variability was observed in the nucleotide sequences of the S3 gene, whereas the deduced amino acid sequences of the S3 gene product, sigma NS, were highly conserved. When variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 0 publications
2
45
0
Order By: Relevance
“…Reovirus genomic dsRNA was purified from second-passage L-cell lysate stocks by previously described techniques (15). Oligodeoxynucleotide primers 5Ј-AAGTCACGCCTGTCGTCGTC-3Ј and 5Ј-A CCACCAAGACACCGGCACA-3Ј, which correspond to the 5Ј and 3Ј termini of the S3 gene, respectively, were used to generate cDNA clones from genomic dsRNA.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Reovirus genomic dsRNA was purified from second-passage L-cell lysate stocks by previously described techniques (15). Oligodeoxynucleotide primers 5Ј-AAGTCACGCCTGTCGTCGTC-3Ј and 5Ј-A CCACCAAGACACCGGCACA-3Ј, which correspond to the 5Ј and 3Ј termini of the S3 gene, respectively, were used to generate cDNA clones from genomic dsRNA.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…All 12 of the 1E1-and 5C6-resistant mutants for which S1 sequences were determined contained these two additional nucleotide changes relative to the published T1L S1 sequences and were thus identical to their parents in that regard. (20,23). The results for reoviruses T1L, T2/simian/Maryland/ SV59/1958 (T2S59), and T3D, evaluated for neutralization by 1E1 in an identical manner, were previously reported (24) and were added to this figure for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…The plaque reduction assay in cell culture is the classical method for demonstrating antibody-mediated neutralization of viral particles (57). We used this assay to test the neutralizing capacity of 1E1 with several additional reovirus isolates (20,23) than previously tested (24) in L929 cells. The results demonstrated that 1E1 neutralizes the two newly tested type 1 isolates, but neither of the two newly tested type 2 isolates nor the two newly tested type 3 isolates (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the S 1 gene of MRV belonging to different serotypes has shown a strict correlation between sequence similarity and viral serotype [34,56,117]. Conversely, the other genome segments do not display any correlation to viral serotype, suggesting that MRV have evolved independently of serotype in the various species [25,37,71,87,94].…”
Section: Canine Reovirusmentioning
confidence: 99%